The actor as a director of himself (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
When we write about the actor’s work, we tend to focus on what he does or how he does what he does. I’d like here to put the focus on where the actor does what he does. By this I am affirming that the perception of where I am constitutes what I do and how I do. This where can be the physical space of the stage, the light, the architecture, as much as the conception of mise-en-scene, the conventions, the poetic universe where I enter to find the way and the tone of the work. Thinking on the where blurs the limits between the actors and the directors work, because it impels the actor to assume the choices of what is around him, choices that historically are made exclusively by the director.
Keywords: presentación teatral; theatrical performance; theatrical convention